Community Empowerment Model Through Village Intitutions To Organize Events : Studies In Tourism Pilot Areas - Apri Kuntariningsih; Yustina Denik Risyanti; Sapto Supriyanto; Hartoyo Soehari (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
The Indonesian tourism industry is very important for development because it can increase its contribution to gross domestic product (GDP). Recently, community-based tourism (CBT) has developed, which refers to a type of sustainable tourism. Community-based tourism aims to create a fairer distribution of tourism income, improve cultural preservation, and increase environmental protection by directly involving local communities in tourism management. The aim of the research is to determine community empowerment through village institutions to organize events, in a tourism village pilot as a case study. Qualitative research that focuses on community empowerment where the informants in this research are village heads, village officials, Pokdarwis administrators, tourism village managers, and economic driving community groups. The research results show that although production, accommodation and accessibility units have not yet been formed, the division of labor with reference to the main tasks and functions of each institution in the tourism village pilot, has produced culinary products, arts groups and agro-tourism areas.